2018
DOI: 10.1021/acs.chemmater.8b02511
|View full text |Cite
|
Sign up to set email alerts
|

Structure Transformation of a Luminescent Pillared-Layer Metal–Organic Framework Caused by Point Defects Accumulation

Abstract: Pillared-layer metal–organic frameworks (MOFs) are often encountered to “collapse” upon external stimuli due to weak interactions between the layers and the pillars. However, the detailed local structural change, especially the accumulation of defects due to intricately disordered bond dissociations, is not clear due to the complicated and dynamic nature of the collapse. We report a luminescent pillared-layer MOF structure, FDM-22, using zinc dicarboxylates as layers and dipyridyl ligands as pillars, in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 40 publications
3
25
1
Order By: Relevance
“…Compared to the as‐synthesized YNU‐1 sample, powder X‐ray diffraction patterns showed that the sharp diffraction peaks diminished after transforming into YNU‐1 nanobelts, thereby revealing that the partly crystal structure changed after the water treatment (Figure A). This phenomenon was similar to the previous report on MOFs with phase transformation, in which the XRD pattern also completely changed in comparison to that of the original MOF . Unfortunately, owing to the low solubility of QBA in water, it was difficult to obtain a single crystal of YNU‐1 nanobelts.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Compared to the as‐synthesized YNU‐1 sample, powder X‐ray diffraction patterns showed that the sharp diffraction peaks diminished after transforming into YNU‐1 nanobelts, thereby revealing that the partly crystal structure changed after the water treatment (Figure A). This phenomenon was similar to the previous report on MOFs with phase transformation, in which the XRD pattern also completely changed in comparison to that of the original MOF . Unfortunately, owing to the low solubility of QBA in water, it was difficult to obtain a single crystal of YNU‐1 nanobelts.…”
Section: Resultssupporting
confidence: 88%
“…Specifically,t he peaks at 1137.531,1 131.67,a nd 1134.62 eV correspond to the 6, 8, and 9-coordinated Eu, respectively ( Figure S10C). [38] The percentages of 8-coordinated Eu (from 5.79 to 29.98 %) clearly increased after water treatment, thusi ndicating that the coordination bonds of Eu cations with QBA ligandsw ere partly replaced by water molecules. The deconvolution of Or egionsr evealed the presence of two distinct Op eaks for both samples (Figure S10D).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Multicomponent MOFs have emerging applications in catalysis, luminescence and gas storage . In order to form multicomponent MOFs judicious selection of the linkers is essential (Figure , Scheme S1) .…”
Section: Introductionmentioning
confidence: 99%